Territórios de cultura: potencialidades de luta e recuperação na análise do discurso de lideranças culturais de grupos pernambucanos - Gabriela Vilas Boas Ornelas (2019)
The territories of cultural groups are loaded with symbolic dominance as a function of the network of created meanings. The multiplicity and variation inherent in culture enclose the power of appropriation, that is, they bring use value to these groups territories, adding to them marks of the lived space. Based on that, can we understand culture beyond distraction and think of it as a strategic element in strengthening territories and their struggles? We aim to understand how the appropriation of the cultural element by peripheral cultural groups affects the ways of acting in the space, attaching a meaning to it and weaving relationships. We conducted semi-structured interviews with cultural leaders from two groups from the state of Pernambuco, Brazil, in 2018: Coco de Umbigada and Maracatu Nação Cambinda Estrela, located in the urban peripheries of Olinda and Recife, respectively. Based on the interviewees' speeches, we bring together the territory as a geographic category and the existing literature through the discourse analysis in the works of ORLANDI (2007) and PÊCHEUX (1996; 1988). We find that, in these territories, there is room for culture, education, religion and social composition, and that struggles are organized in a specific way, through strategies appropriate to external relations and protective of what is dear to these groups in terms of symbolism. Thus, we can argue that the presence of culture spreads out and organizes life through the recovery-insurgency dichotomy associated with the construction of a local political reference, a space where one can ask for help and feel integrated.